IMPROVING THE EFFICIENCY OF PAYMENT SYSTEMS IN COMMERCIAL BANKS AND ENSURING THEIR SECURITY (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The article examines issues related to improving the efficiency of payment systems in commercial banks of the Republic of Uzbekistan and ensuring their security in the context of the digital transformation of the banking sector. Based on an analysis of statistical data for 2020–2024, trends were identified in the growth of electronic and mobile payments, the expansion of non-cash transactions, and the development of payment card infrastructure.